Home and identity in nineteenth-century literary London - Robertson, Lisa C. (Edinburgh University Press, 2020)
This book brings together a range of new models for modern living that emerged in response to social and economic changes in nineteenth-century London, and the literature that gave expression to their novelty.
Keywords: English literature -- England -- London -- History and criticism.; English literature -- 19th century -- History and criticism.; Home in literature.; Identity (Philosophical concept) in literature.; Dwellings -- England -- History -- 19th century.; London (England) -- In literature.; London (England) -- Social life and customs -- 19th century.; Littérature anglaise -- Angleterre -- Londres -- Histoire et critique.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Foyer dans la littérature.; Identité dans la littérature.; Habitations -- Angleterre -- Histoire -- 19e siècle.; Londres (Angleterre) -- Mœurs et coutumes -- 19e siècle.; Dwellings; English literature; Home in literature; Identity (Philosophical concept) in literature; Literature; Manners and customs; England; England -- London; 1800-1899; Criticism, interpretation, etc.; History